Auditoria regular al municipio de La Tebaida vigencia 2014 (2015)
This paper brings up the work carried out in form of internship with the Comptroller General of Quindío, within the area of fiscal control, for which the review of the financial statements and the surrender of the entire account by the Municipality held the effect Tebaida 2014. The review described, was executed in accordance with the expressed in the guide territorial audit (GAT) issued by Dr. Sandra Morelli Rico in November of 2012, this being the main guideline under which territorial comptrollers, conducted the review operations carried out by the agencies of Central, State and Municipal Government in fulfilling its legal powers, to finally give an opinion on the efficient use of public resources and the achievement of the objectives of the entity , and finally to allow greater effectiveness and timeliness in achieving the results generated by the audit process.